Implementasi Kebijakan Dana Desa di Desa Deli Muda Hulu Kecamatan Perbaungan Kabupaten Serdang Bedagai - Gunawan Jaya Wardana Hasibuan; Badaruddin Badaruddin; Heri Kusmanto (PERSPEKTIF, 2022)
The purpose of this study is to provide an overview of the implementation of the Village Fund in Deli Muda Hulu Village, Perbaungan District, Serdang Bedagai Regency, as well as the supporting and inhibiting factors that affect the implementation and strategies that must be carried out in the context of successful policy implementation. in the management of the Village Fund. The method used in this study is a qualitative descriptive method, where the main instrument in the study is the researcher himself. In this study, the authors also used survey research to obtain primary data on village fund policies in Deli Muda Hulu Village, Perbaungan District, Serdang Bedagai Regency. The results showed that the implementation of the Village Fund (DD) policy in Deli Muda Hulu Village, Perbaungan District, Serdang Bedagai Regency went quite smoothly. However, when it comes to achieving goals, the implementation of the Village Fund (DD) in Deli Muda Hulu Village, Perbaungan District, Serdang Bedagai Regency is not yet optimal. Although the goal of improving governance, development and community administration has been carried out optimally, the aim of increasing the capacity of community institutions in the village in planning, implementing and controlling development has not been optimal. Likewise, the goal of increasing community self- help participation has not been optimal. Several factors that influence the implementation of the Village Fund (DD) in Deli Muda Hulu Village, Perbaungan District, Serdang Bedagai Regency are communication, resource capabilities, attitude of implementers, bureaucratic structure, environment and policy size and objectives.